Organocatalytic trans Phosphinoboration of Internal Alkynes. (1st July 2020) - Fritzemeier, Russell G.; Nekvinda, Jan; Vogels, Christopher M.; Rosenblum, Carol Ann; Slebodnick, Carla; Westcott, Stephen A.; Santos, Webster L.
Abstract: We report the first trans phosphinoboration of internal alkynes. With an organophosphine catalyst, alkynoate esters and the phosphinoboronate Ph2 P‐Bpin are efficiently converted into the corresponding trans ‐α‐phosphino‐β‐boryl acrylate products in moderate to good yield with high regio‐ and Z ‐selectivity. This reaction operates under mild conditions and demonstrates good atom economy, requiring only a modest excess of the phosphinoboronate. X‐ray crystallography experiments allowed structural assignment of the unprecedented and densely functionalized ( Z )‐α‐phosphino‐β‐boryl acrylate products. Abstract : PB&J? Phosphinoboration across a triple bond catalyzed by tributyl phosphine was achieved. The trans ‐α‐phosphino‐β‐boryl acrylate products are obtained in moderate to good yield with high regio‐ and Z ‐selectivity. This reaction operates under mild conditions and demonstrates good atom economy, requiring only a modest excess of the phosphinoboronate.